Laboratory management system (LMS) - Hasrul Harfizal, Mohd Zait (2011)
Nowadays, many application system use online system to interact with the user.It is because online system has many advantages rather than using manual system.Laboratory Management System is an example of online system that will be develop for lab administrators to manage the labs.In this project,several modules will be applied to the lab management system. All these modules are choosing based on the lab administrator and user request.This project has its objectives and problem statements that give the reason why this online system should be develop.Before developing the project,the developers should make a plan that consist the objectives, problem statements,scopes,and methodology including the system analysis,system design and system requirement that will used.All these components will helps the developers what should they develops and how to develops the system.